(untitled) (American Journal of Public Diplomacy and International Studies (2993-2157), 2025)
This article discusses the important role of Uzbekistan’s public diplomacy in developing international relations, strengthening cultural exchanges, and expanding cooperation with foreign countries. It highlights how initiatives such as international forums, cultural festivals, and educational partnerships contribute to enhancing Uzbekistan’s global reputation and fostering mutual understanding. Additionally, economic agreements with the European Union, China, and Russia are presented as key factors that further support diplomatic efforts. Public diplomacy not only promotes cultural and economic development but also plays a crucial role in ensuring international security and stability by reinforcing cooperation between nations.